Growth-oriented entrepreneurship - Gutterman, Alan S. 1955- (Entrepreneurship and small business management collection, 2018)
1. Growth-oriented entrepreneurship -- 2. Innovation clusters -- 3. Emerging companies -- About the author -- Index